Chromosome-level genome assembly of Microplitis manilae Ashmead, 1904 (Hymenoptera: Braconidae) - Xiaohan Shu; Ruizhong Yuan; Boying Zheng; Zhizhi Wang; Xiqian Ye; Pu Tang; Xuexin Chen (Scientific Data, 2023)
Abstract Microplitis manilae Ashmead (Hymenoptera: Braconidae) is an important parasitoid of agricultural pests in lepidopteran species. So far, two extant genome assembles from the genus Microplitis are fragmented. Here, we offered a high-quality genome assembly of M. manilae at the chromosome level with high accuracy and contiguity, assembled by ONT long-read, MGI-SEQ short-read, and Hi-C sequencing methods. The final assembled genome size was 282.85 Mb, with 268.17 Mb assigned to 11 pseudochromosomes. The scaffold N50 length was 25.23 Mb, and the complete BUSCO score was 98.61%. The genome contained 152.37 Mb of repetitive elements, representing 53.87% of the total genome size. We predicted 15,689 protein-coding genes, of which 13,580 genes were annotated functionally. Gene family evolution investigations of M. manilae revealed 615 expanded and 635 contracted gene families. The high-quality genome of M. manilae reported in this paper will be a useful genomic resource for research on parasitoid wasps in the future.